Poly-β-Hydroxybutyrate Production by the Cyanobacterium Scytonema geitleri Bharadwaja under Varying Environmental Conditions - Manoj K. Singh; Pradeep K. Rai; Anuradha Rai; Surendra Singh; Jay Shankar Singh (Biomolecules, 2019)
The production of poly-β-hydroxybutyrate (PHB) under varying environmental conditions (pH, temperature and carbon sources) was examined in the cyanobacterium Scytonema geitleri Bharadwaja isolated from the roof-top of a building. The S. geitleri produced PHB and the production of PHB was linear with the growth of cyanobacterium. The maximum PHB production (7.12% of dry cell weight) was recorded when the cells of S. geitleri were at their stationary growth phase. The production of PHB was optimum at pH 8.5 and 30 °C, and acetate (30 mM) was the preferred carbon source.